Alexithymia Is a Key Mediator of the Relationship Between Magical Thinking and Empathy - Eddy, Clare M.; Hansen, Peter C. (Frontiers in Psychiatry, 2021)
Thought action fusion (TAF), whereby internal thoughts are perceived to exert equivalent effects to external actions, is a form of magical thinking. Psychiatric disorders associated with TAF (e.g. schizophrenia; obsessive compulsive disorder) can feature social cognitive abnormalities. We explored relationships between TAF and empathy in 273 healthy young adults. TAF was directly correlated with higher personal distress, but not perspective taking, fantasy or empathic concern. TAF moral (the belief that thinking about an action/behaviour is morally equivalent to actually performing that behaviour) was predicted by emotion contagion, alexithymia and need for closure. TAF likelihood (the belief that simply having a thought about an event makes that event more likely to occur) was predicted by personal distress, sense of agency and alexithymia. Both cognitive (TAF and negative sense of agency) and emotional (emotion contagion, alexithymia) factors contributed to personal distress. TAF, negative sense of agency and personal distress mediated the effect of emotion contagion on alexithymia. Our findings reveal complex inter-relationships between emotional processes and TAF, shedding further light on the social cognitive deficits seen in disorders associated with magical thinking. Furthermore, they emphasise the potential importance of alexithymia and emotion contagion as mediators or potential risk factors in the development of psychiatric symptoms linked to TAF, such as intrusive thoughts about harm to others.